EKSTRAKSI DNA Collocalia fuchiphaga DENGAN METODE PHENOL CHLOROFORM EXTRACTION DARI BERBAGAI MATERIAL SUMBER GENETIK - Hendra, Hendra; Suryaningtyas, Natalia Widya Yuda; Riyanto, Cellica; Heryanto, Aditya Fendy (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2013)
DNA extraction is the first important step in molecular study. The aim of this research was to compare DNA extraction protocols, PCE and extraction kit for each genetic material sources (blood and feathers). For PCE method, we used three different extraction buffer. This study suggested that PCE method was more efficient than the extraction kit method. Meanwhile, extraction buffer 2 was more efficient for extracting feather DNA, while extraction buffer 3 was more efficient for extracting blood DNA. Wing feather was a favorable sample as genetic source for DNA extraction.Â Keywords: DNA extraction, phenol-chloroform, Collocalia fuchiphaga